Faktor – Faktor Yang Memengaruhi Earnings Response Coefficient - Ivon, Widyasari (Jurnal Paradigma Akuntansi, 2022)
The purpose of this research is to gain empirical evidence about the effects firm size, profitability, leverage, capital structure, and earnings growth on earnings response coefficienton manufacturing companies listed in Indonesia Stock Exchange for 2017-2019. This research used a sample of one hundred and eighty manufacturing companies. The result of this research indicate that the firm size does not have an effect on earnings response coefficient, profitability does not have an effect on earnings response coefficient, leverage have an effect on earnings response coefficient, capital structure have an effect on earnings response coefficient and earnings growth does not have an effect on earnings response coefficient. To get a better results, further research is use of other variables that effect the practise of earnings response coefficient.